STUDI KARAKTERISTIK TERMAL BRIKET ARANG KULIT BUAH KAKAO - Patabang, Daud (Jurnal MEKANIKAL, 2011)
Background of this investigation is reasoned by fuel consumptions focusing on oil and gas which they are limited resource energy and its cost rising any time. On the other side,  available of biomass energy  is still overflow and within renewable resources. This research investigates thermal characteristic’s of cacao char briquette that consists of High Heating Value (HHV), Volatile Matters (VM), Moisture (M), Ash (A), thermal efficiency and emission gas of real combustions on briquette stove. The result of investigations are; HHV=6308.207 kcal/kg, VM=58,75%, M=3.27%,A=23.53%, FC= 25.55%, maximum thermal efficiency is 35.67% and emissions gas consist of CO and CO2 are  safe of  human being according to WHO Standard.